Evaluation of PDKB Performance's Impact on SAIDI SAIFI at PT. PLN UP3 Langsa - Is, Muhazir; Tarmizi, Tarmizi; Adriman, Ramzi (PTE FTK UIN Ar-Raniry, 2025)
The reliability of the electricity distribution system is essential to ensure continuous service to consumers. Maintenance is necessary to uphold this reliability. However, on the SUTM (Medium Voltage Overhead Line) network, maintenance often requires power outages, causing losses for both consumers and the company due to undelivered electrical energy (kWh). This study aims to analyze the SAIDI and SAIFI values, as well as the amount of kWh before and after implementing PDKB (Live Line Maintenance) at PT PLN (Persero) UP3 Langsa. The research uses a quantitative descriptive method with data collected through observation and analysis of kWh, SAIDI, and SAIFI metrics. The results show that PDKB-based maintenance saved 1,457,823.97 kWh with a financial gain of Rp. 1,135,391,541.48. The SAIDI and SAIFI values were 819.456 minutes/customer and 9.29 times/customer, respectively. In contrast, maintenance without PDKB resulted in a loss of 3,921,103.2 kWh or Rp. 3,136,882,560, with higher SAIDI and SAIFI values of 1533.84 minutes/customer and 10.04 times/customer. These findings indicate that lower SAIDI and SAIFI values reflect improved service quality, enhancing the company’s image and reducing losses from power distribution interruptions